Five-Factor Personality Inventories Have a Competence-Related Higher-Order Factor Due to Item Phrasing - Bäckström, Martin; Björklund, Fredrik; Persson, Rebecka; Costa, Ariela (Frontiers in Psychology, 2020)
This research examines whether the items of some of the most well-established five-factor inventories refer to competence. Results reveal that both experts and laymen can distinguish between items that refer to how competently a behavior is performed and items that do not (Study 1). Responses to items that refer to competence create a higher-order factor in the personality inventories (Study 2), and the variability in responses to competence-related items in personality self-ratings is best modeled as a general factor rather than as also tied to the specific Big Five factors (Studies 3 and 4). We suggest that a focused debate on what personality items should refer to is likely to have considerable positive consequences for both theory and measurement of personality.